1991
DOI: 10.1177/074171369104200104
|View full text |Cite
|
Sign up to set email alerts
|

Civic Education: An Adult Education Imperative

Abstract: The proposition is argued that the primal contribution of adult education in a democracy, before all other purposes it serves, is civic education. A corollary position is that reluctance to facilitate citizen understanding of civic problems and skillful participation in solutions leaves adult education agencies on the sidelines in this most important sphere of adult life and furthers the current American retreat to privatism. Conditions affecting the substance of adult civic education are described. The possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 8 publications
0
12
0
4
Order By: Relevance
“…Boggs (1991) suggested, "Civic knowledge, skill, and the disposition to use them to achieve a desired vision of the community can be furthered through purposefully structured civic education" (p. 53). The LEAR program was structured after community leadership models currently being run by cooperative extension divisions of major universities; those models were characterized by highly experiential learning and discovery methods and materials.…”
Section: Description Of Program and Methodsmentioning
confidence: 98%
“…Boggs (1991) suggested, "Civic knowledge, skill, and the disposition to use them to achieve a desired vision of the community can be furthered through purposefully structured civic education" (p. 53). The LEAR program was structured after community leadership models currently being run by cooperative extension divisions of major universities; those models were characterized by highly experiential learning and discovery methods and materials.…”
Section: Description Of Program and Methodsmentioning
confidence: 98%
“…It contributes to a small but growing body of literature on adult learning and civic engagement, providing one of very few accounts of participant learning as an outcome of involvement in official policy production within institutions. Like the research conducted in other jurisdictions (Boggs, 1986;Biesta, 2005;Lerner & Schugurensky, 2007;Schugurensky & Myers, 2008;Pinnington et al, 2009), Ontario policy actors interviewed for this research reported positive gains in learning as a direct result of participation. Some of their experiences approached agonistic deliberation unintentionally, despite procedural shortcomings that neither achieved PPA nor agonistic deliberation criteria.…”
Section: Resultsmentioning
confidence: 93%
“…Empirical research on the educational dimension of civic participation is in its infancy (Schugurensky, 2010), though some evidence of learning as an outcome of civic participation has been published, primarily reporting how informal learning occurs through participation in spaces of deliberation and decision making (Boggs, 1986;Biesta, 2005;Schugurensky & Myers, 2008). Much of this growing body of literature is situated within participatory policy analysis (PPA).…”
Section: Background: Civic Participation Learning and Democracymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key strategies for reducing human-wolf conflicts is to train local communities on how to coexist with wolves and prevent conflicts (Boggs, 1991). Instruction in proper waste management, informing the general public of wolf behavior, and how to reduce food attractants are important steps for reducing predatory attacks in these areas.…”
Section: Discussionmentioning
confidence: 99%